Comportamiento agronómico y de producción de cuatro hortalizas de fruto con tres abonos orgánicos en la hacienda Tecnilandia – Quevedo. - Holguín Sellan, Miguel Antonio (2013)
This research was conducted at the Tecnilandia Hacienda, located at kilometre 11 Via the joint right margin; belonging to the Canton Quevedo, Los Ríos province. Its geographical location is 6´ South latitude and 79th 01o 29 ´ West longitude, with an altitude of 74 (m), a complete block design to the random (DCA) composed of five treatments and three replicates was used, the treatments were: tomato H1, H2 pepper, cucumber H3 and H4 Eggplant; fertilizers A1. 100% Earthworm humus, A2. 100% Water hyacinth and A3. 50% Water 50% hyacinth Humus de Lombriz.The results were: the variable height of the tomato, expresses that 30, 45 and 60 days the highest was 50% treatment water hyacinth 50% with 71.60 worm Humus; 90.27 and 119.40 cm. The number of fruits per harvest sets that the control treatment obtained the highest average of fruits to the first and fourth harvest with 2.50 and 2.80 fruits respectively; the second water hyacinth harvested treatment 50% 50% Humus de Lombriz with 2.89 fruits; in the third harvest the Humus de Lombriz with 2.83 treatment fruits. The diameter of tomato according to harvest are detailed in table 11. Stands to Humus de Lombriz treatment and 50% water hyacinth 50% Humus de Lombriz reached higher averages in the first harvest with 8.42 cm each; in the second harvest Humus de Lombriz treatment obtained the highest average with 8.35 cm; for the third harvest therapy with 7.38 water hyacinth cm and the fourth harvest treatment witness with 7.27 cm. For the weight of fruit in the first and third harvest treatment water hyacinth achieved greater weight with 172.28 and 178.62 g in your order, existing statistical differences among treatments at the first harvest; the second water hyacinth harvested treatment 50% 50% Humus de Lombriz with 179.20 g; for the fourth harvest treatment witness with 271.72 g..................................................